2022
DOI: 10.1093/jmammal/gyac024
|View full text |Cite
|
Sign up to set email alerts
|

Variation in diet of frugivorous bats in fragments of Brazil’s Atlantic Forest associated with vegetation density

Abstract: Species distribution and persistence have long been known to vary with landscape structure; however, continued human activities in altered landscapes raise many questions as to how habitat fragmentation impacts the biology of persistent animal populations. Using carbon and nitrogen stable isotope analysis, we examined interspecific variation in the diet of frugivorous bats among remnant habitat patches of Brazil’s Atlantic Forest. We hypothesized that the diet of individuals captured in habitat patches would b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Vegetation may drive the fine-scale spatial distribution of sympatric species by dictating the availability of resources at multiple scales ( Kubiak, Galiano & de Freitas, 2015 ), both spatial and temporal. Drawing on markedly different studies in the same forest type highlights the importance of vegetation; in Brazil’s Atlantic Forest, bat diet was best explained by landscape composition, particularly vegetation density ( Oelbaum et al, 2022 ), while in the same forest, the diversity of ants was explained by a combination of shrub leaf density and tree circumference ( Sampaio et al, 2023 ). Among macropods, Le Mar & Mcarthur (2005) showed that sympatric wallabies in Tasmania had similar food requirements and foraged in the same habitats by night, but that their selection of daytime refuges differed markedly, probably due to their contrasting predator avoidance strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation may drive the fine-scale spatial distribution of sympatric species by dictating the availability of resources at multiple scales ( Kubiak, Galiano & de Freitas, 2015 ), both spatial and temporal. Drawing on markedly different studies in the same forest type highlights the importance of vegetation; in Brazil’s Atlantic Forest, bat diet was best explained by landscape composition, particularly vegetation density ( Oelbaum et al, 2022 ), while in the same forest, the diversity of ants was explained by a combination of shrub leaf density and tree circumference ( Sampaio et al, 2023 ). Among macropods, Le Mar & Mcarthur (2005) showed that sympatric wallabies in Tasmania had similar food requirements and foraged in the same habitats by night, but that their selection of daytime refuges differed markedly, probably due to their contrasting predator avoidance strategies.…”
Section: Introductionmentioning
confidence: 99%